DESIGN AND IMPLEMENTATION OF TRAJECTORY DATA MANAGEMENT AND ANALYSIS TECHNOLOGY FRAMEWORK BASED ON SPATIOTEMPORAL GRID MODEL - J. Li; J. Q. Liu; X. L. Mei; W. T. Sun; Q. Huang; Y. Y. Zhang; L. W. Qiao; C. Y. Zhang (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
The trajectory data generated by various position-aware devices is widely used in various fields of society, but its conventional vector representation and various analysis algorithms based on it have high computational complexity. This makes it difficult to meet the application requirements of real-time or near real-time management and analysis of large-scale trajectory data. In view of the above challenges, this paper proposes a trajectory data management and analysis technology framework based on the Spatiotemporal Grid Model (STGM). First, the trajectory data is represented by spatiotemporal grid encoding instead of vector coordinates, and it can achieve dimensionality reduction and integrated management of high-dimensional heterogeneous trajectory data. Second, the trajectory computing and analysis methods based on STGM are introduced, which reduce the computing complexity of algorithms. Furthermore, various types of trajectory mining and applications are realized on the basis of high-performance computing technologies. Finally, a trajectory data management and analysis prototype system based on the STGM is developed, and experimental results verify the reliability and effectiveness of the proposed technology framework.